The Orient in Chaucer and medieval romance - Heffernan, Carol Falvo (Studies in medieval romance., 2003)
The Orient is a major motif in Chaucer and medieval romance and this study reveals much about its use and significance, offering fresh readings of a number of texts. These include the legend of Constance, where the mercantile details of the eastern Mediterranean reinforce the setting; the portraits of Cleopatra and Dido from the Legend of Good Women; details in the Squire's Tale; and aspects of orientalism in the Middle English 'Floris and Blauncheflur' and 'Le Bone Florence of Rome', the latter related to analogous oriental tales about heroic women who remain steadfast in virtue.